ANALISIS FAKTOR PENERIMAAN TEKNOLOGI TERHADAP PENGGUNAAN REKAM MEDIK ELEKTRONIK (RME) DENGAN MODEL TAM - Minggu, Irvan Susyanto; Adam, Arlin; Alim, Andi (Jurnal Ilmiah Kesehatan Media Husada, 2026)
Digital transformation in the health service system requires the implementation of Electronic Medical Records (RME) in all health service facilities, including in remote areas such as the Bokondini Community Health Center, Tolikara Regency. However, RME implementation faces various challenges, including limited infrastructure, technology access, and user readiness. This research aims to analyze the relationship between Perceived Ease of Use (PEOU), Perceived Usefulness (PU), and Attitude Toward Using (ATU) on Actual Usage (AU) in the use of RME based on the Technology Acceptance Model (TAM) approach. This research uses a cross-sectional design with a descriptive quantitative approach. A total of 24 health workers at the Bokondini Community Health Center were included as respondents using the total sampling method. Data was collected using a questionnaire that had been tested for validity and reliability, then analyzed using the Chi-Square test with a significance level of 0.05. The results showed that there was a significant relationship between PEOU (p = 0.045), PU (p = 0.019), and ATU (p = 0.017) on AU. It can be concluded that perceived ease of use, perceived usefulness, and positive attitudes of users towards technology play an important role in driving actual use of RME. Therefore, efforts to increase digital literacy, training and providing infrastructure are strategic steps in supporting the successful implementation of RME, especially in disadvantaged and hard-to-reach areas